Maqashid Syariah as a Basis for Establishing Decree in Indonesia - Yusdiansyah, Efik; Iskandar, Rusli K.; Hendar, Jejen (KnE Social Sciences, 2023)
In the governance of a country, the government plays a vital role in establishing regulations and policies. These decisions are made by state administrative officials in accordance with the provisions of laws and regulations, with the ultimate goal of creating good governance. In Indonesia, being a country with a Muslim majority, Islamic values can also be integrated into the government’s operations. One such value is the principle of Maqasid Sharia, which serves as the basis and purpose in Islamic law. This principle encompasses three main objectives, which are Dharuriyah (necessities), Hajjiyah (needs), and Tahsiniyah (enhancements). To explore this further, normative judicial research methods are utilized, focusing on primary legal materials, and employing deductive methods for analysis. By doing so, the principle of maqasid sharia can be utilized as a model for state administrative officials, particularly those who adhere to Islamic beliefs, in their decision-making processes. Keywords: administrative decrees, Maqashid Sharia, State Administrative Law